Predation on Atlantic herring (Clupea harengus) eggs by the resident predator community in coastal transitional waters. (18th May 2017) - Kotterba, Paul; Moll, Dorothee; Hammer, Cornelius; Peck, Myron A.; Oesterwind, Daniel; Polte, Patrick
Abstract: Atlantic herring ( Clupea harengus ) migrates from offshore to coastal areas to spawn and their eggs and larvae may substantially increase prey resources for resident predators. We combined an in situ predator exclusion experiment using eggs naturally spawned on submerged aquatic vegetation and field observations of predator abundance to estimate the magnitude of predation mortality of herring eggs. During our predator exclusion experiment, performed in an important spawning ground in the southwest Baltic Sea, 20% of the herring eggs were consumed resulting in an extrapolated predation of 42% of all eggs between spawning and hatch. Abundance and stomach content analyses indicated that one predator (threespine stickleback, Gasterosteus aculeatus ) was responsible for the majority of the predation impact. Predation mortality estimates from this in situ study were more than 10‐fold higher than those of an empirical egg predation model for the same predator in the same region. Our findings highlight the potential of resident predators to regulate the survival of early life stages of ocean‐going fishes that rely on the nursery functions of inshore transitional waters.